Craig Rhos-y-felin: a Welsh bluestone megalith quarry for Stonehenge. (7th December 2015) - Parker Pearson, Mike; Bevins, Richard; Ixer, Rob; Pollard, Joshua; Richards, Colin; Welham, Kate; Chan, Ben; Edinborough, Kevan; Hamilton, Derek; Macphail, Richard; Schlee, Duncan; Schwenninger, Jean-Luc; et al.
Abstract: Abstract : The long-distance transport of the bluestones from south Wales to Stonehenge is one of the most remarkable achievements of Neolithic societies in north-west Europe. Where precisely these stones were quarried, when they were extracted and how they were transported has long been a subject of speculation, experiment and controversy. The discovery of a megalithic bluestone quarry at Craig Rhos-y-felin in 2011 marked a turning point in this research. Subsequent excavations have provided details of the quarrying process along with direct dating evidence for the extraction of bluestone monoliths at this location, demonstrating both Neolithic and Early Bronze Age activity.